Morpho-cultural, pathogenic, and genetic characterization of Indian isolates of Macrophomina phaseolina causing charcoal rot in soybean - Laxman Singh Rajput; Sanjeev Kumar; Kriti Pathak; Palak Acharya; Divyanshu Goswami; Vennampally Nataraj; Maranna Shivakumar; Hemant Singh Maheshwari; Saloni Mandloi; Sapna Jaiswal; Asha Yadav; Raksha Vishwakarma (Heliyon)
Macrophomina phaseolina, a devastating soil and seed-borne fungus causing charcoal rot in soybean, poses a significant challenge to soybean production and breeding programs across all major soybean-growing regions of India. Fifty-five M. phaseolina isolates were collected from India's eight diverse soybean-growing agroecological regions. These isolates were examined for morpho-cultural, molecular, and pathogenic variability. All these isolates were pathogenic to the soybean and had significant variability for different Morpho-cultural characters. Principal component analysis (PCA) showed that most of Morpho-cultural traits are not having association with pathogenic traits. Cluster analysis showed that all these 55 isolates of M. phaseolina were classified into two major groups, and virulence characters did not separate based on origin. Group B showed more diversity and included the most virulent pathogen isolates. Phylogenetic analysis of the Internal Transcribed Spacer (ITS), a conserved rDNA region, revealed limited diversity among the 55 isolates. Irrespective of morpho-cultural and pathogenic characters, most isolates (n = 52) were clustered in a group. Pathogenic variability analysis has revealed region specific most virulent isolate from diverse agroecological regions of India. GGE biplot segregated the main effect of each component, cultivars (G), isolates (I), and G × I interactions with significant levels (p < 0.001). The virulence of isolates contributed 56.30 % of the total variation, followed by varieties (36.79 %) and G × I interaction (4.96 %). GGE biplot also provides information on two highly discriminative isolates. These isolates may be useful for screening genotypes and identifying quantitative trait loci (QTL) linked to soybean charcoal rot.